Theoretical-methodological aspect of personality’s creativity studying [Теоретико-методологический аспект исследования креативности личности] (in Russian) - Ivanchenko, Andreyanna; Иванченко, Андреянна Алексеевна; Іванченко, Андреянна Олексіївна (К. : ДП «Інформаційно-аналітичне агенство», 2010)
In this paper a theoretical analysis of the creativity notion is carried out. A conceptual methodological approach for creativity studying is elaborated. Theoretical conceptions of creativity psycological essence are widened. The dynamic character of the creativity process and its significance for the passage to a qualitatively improved level of life are shown. В статье осуществлен теоретический анализ понятия креативности. Разработан концептуально-методологический подход к ее исследованию. Расширены теоретические представления о ее психологической сущности. Показан динамический характер креативного процесса и значимость креативности для перехода личности на качественно улучшенный уровень жизни. У статті здійснено теоретичний аналіз поняття креативності. Розроблено концептуально-методологічний підхід до її дослідження. Розширені теоретичні уявлення про її психологічну сутність. Показано динамічний характер креативного процесу та значимість креативності для переходу особистості на якісно поліпшений рівень життя. In this paper a theoretical analysis of the creativity notion is carried out. A conceptual methodological approach for creativity studying is elaborated. Theoretical conceptions of creativity psycological essence are widened. The dynamic character of the creativity process and its significance for the passage to a qualitatively improved level of life are shown.
Keywords: креативність; теоретико-методологічний; духовність; системність; самоорганізація; creativity; dynamic; theoreticо-methodological; spirituality; self-organization